STUDI LITERATUR: MEDIA PEMBELAJARAN INTERAKTIF DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Dzambiyah, Asfiyatu; Pamungkas, Ahmad Danil; Jamaludin, Ujang; Setiawan, Sigit (PREMIERE : Journal of Islamic Elementary Education, 2024)
Good quality education is essential to produce competent human resources who are able to compete in the global arena. However, challenges in education often hinder effective learning processes so that optimization in the use of learning media is needed to overcome challenges in education and improve learner competence. This study aims to identify and analyze various learning media used in the learning process and their influence on student learning outcomes. The research method used, namely a qualitative approach with a literature study. The research stages include article collection, article reduction, article display, discussion, and conclusion, with data sources in the form of national journal articles in the last five years (2019-2024). The results show that learning media can enrich learners' learning experiences and contribute significantly to improving their learning outcomes. With better understanding, increased brain absorption and stronger memory, learners are able to achieve higher and have a deeper understanding of the material studied. These findings emphasize the importance of optimizing the use of learning media in addressing educational challenges and improving student competencies.